2022
DOI: 10.30526/35.4.2856
|View full text |Cite
|
Sign up to set email alerts
|

Study the Efficiency of Poly Nicotine Amide as Anticorrosion Coating on Stainless Steel and Study Its Biological Activity

Abstract: Using an electrochemical polymerization technique at room temperature, poly nicotine amide (PNA) was produced from the monomer nicotine amide (NA) in aqueous solution. The structure of polymer layer generated on the stainless steel surface (316 L) (working electrode) is investigated by Fourier Transmission Infrared Region (FT-IR). The anti-corrosion activity of polymer coating on the stainless steel (SS 316 L) is investigated by electrochemical polarization in 0.20M solution of HCl at 293-323K. The graphene -m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Figure (9) represents the relationship between Ci/(θ) vs. Ci .Table (3) indicates the values of K ads for the adsorption process in (1 M) of HCl acid at temperatures (303, 313, 323, 333 K).The data given indicate that the adsorption of the inhibitor on the surface of the metal is in great agreement with the Freundlich adsorption model. Increasing the concentration of the inhibitor leads to an increase in the efficiency of the inhibition that is adsorbed on the surface of the metal and blocks the active sites from acid attacks, as well as protecting the metal from corrosion [8] At a constant concentration of the inhibitor, we notice that the K ads equilibrium constant decreases with increasing temperature. therefore, the expected adsorption process on the surface is physical adsorption, and this is consistent with what was found that the inhibition efficiency decreases with increasing temperature [14].the values of the corosion rate can be used to analyze the adsorption mechanism according to Freundlich equation, which was calculated using equation (7) [15] 𝜃 = 𝐾𝑓𝐶𝑖𝑛 …………………………….…”
Section: Inhibitor Performance and Adsorption Interpretationmentioning
confidence: 83%
See 4 more Smart Citations
“…Figure (9) represents the relationship between Ci/(θ) vs. Ci .Table (3) indicates the values of K ads for the adsorption process in (1 M) of HCl acid at temperatures (303, 313, 323, 333 K).The data given indicate that the adsorption of the inhibitor on the surface of the metal is in great agreement with the Freundlich adsorption model. Increasing the concentration of the inhibitor leads to an increase in the efficiency of the inhibition that is adsorbed on the surface of the metal and blocks the active sites from acid attacks, as well as protecting the metal from corrosion [8] At a constant concentration of the inhibitor, we notice that the K ads equilibrium constant decreases with increasing temperature. therefore, the expected adsorption process on the surface is physical adsorption, and this is consistent with what was found that the inhibition efficiency decreases with increasing temperature [14].the values of the corosion rate can be used to analyze the adsorption mechanism according to Freundlich equation, which was calculated using equation (7) [15] 𝜃 = 𝐾𝑓𝐶𝑖𝑛 …………………………….…”
Section: Inhibitor Performance and Adsorption Interpretationmentioning
confidence: 83%
“…The rate was measured by weight loss method using equation (2) [7]The weight difference is a non-electrochemical method for determining corrosion rate and inhibition efficiency that gives more reliable results than electrochemical methods .Because the experimental conditions are dealt with more realistically [8] 𝐶𝑅(𝑀𝑀/𝑌) = (87.6 * ∆𝑊)/𝐷𝐴𝑡……………………… (2) where ∆W (mg) is the weight difference A (cm 2 ) the surface area D (g/cm 3 ) is the density of the mineral…”
Section: ………………………………………(1) W=w I -W F ∆ Wi-wf Represents the Weight ...mentioning
confidence: 99%
See 3 more Smart Citations